Спортсмены-преступники - Raianova A. I. (Relevant lines of scientific research: theory and practice, 2016)
The article illuminates the issues of sports nutrition. Determined notions of nutrition as an important direction in improving the quality of life and optimization of the human motor activity, including in sport and physical culture. The types of sports nutrition depending on the sportsman’s goals is emphasized.
Keywords: спортсмен; криминализация; преступник; athlete; criminal; criminalization and crime among athletes; the type of crime; преступность среди спортсменов; тип преступления